Use of metabolites, metabolithotropic agents and nutritional supplements in sports and sports medicine: a modern view on the problem - I. F. Bielenichev; N. A. Gorchakova; E. Yu. Doroshenko; I. B. Samura; V. P. Ryzhenko; N. V. Bukhtiiarova (Сучасні медичні технології)
Aim. The purpose of this study was to conduct an up-to-date semantic analysis of the results of our own research and literature data on the medical and pharmacological characteristics of metabolites, metabolitotropic agents and nutritional supplements, the peculiarities of their use in sports practice and sports medicine.